5: 3D Transglutaminase Fibronectin Hydrogel Therapy Improves the Healing of Chronic Irradiated Porcine Skin Wounds. (July 2021) - Raghuram, Anjali C.; Yu, Roy P.; Hsu, Jerry F.; Sung, Cynthia; Lo, Andrea Y.; Yao, Jingxin; Manoukian, Haig L.; Wang, Sarah X.; Park, Sun Young; Jiao, Wan; Han, Bo; Wong, Alex K.
Abstract : Purpose: Chronic irradiated wounds are characterized by a delayed and incomplete healing course. Currently, there are no therapies directed at the deficient or dysfunctional biology associated with cutaneous radiation injury. We have previously demonstrated that fibronectin is a key extracellular matrix glycoprotein known to be significantly downregulated in radiation-damaged skin. We further identified that an enzymatically crosslinked hydrogel is a suitable construct for incremental fibronectin release in vitro and in murine wound models. Our present objective was to investigate the design of this fibronectin hydrogel dressing for the treatment of irradiated wounds in the clinically relevant porcine irradiated wound model. Methods: We created a chronic irradiation skin injury model in female Yucatan minipigs. Two 1-month-old minipigs underwent irradiation of the right dorsolateral neck region for 5 consecutive days in 5.5 Gy fractionated doses for a total of 27.5 Gy. Following irradiation, the minipigs were allowed 6 weeks of recovery to enable chronic irradiation skin changes to develop. After recovery, nine 1 cm x 1 cm full-thickness wounds were created in the irradiated fields. After wound creation, 100 μl of fibronectin hydrogel was topically applied on experimental wounds and 100 μl of phosphate-buffered saline (PBS) hydrogel was applied on control wounds. Standardized wound photographs were taken at weekly time intervals to calculate the percentage of wound closure relative to original wound size. Tissues isolated from the wound areas were evaluated histologically for wound healing quality and analyzed for gene and protein levels of radiation injury mediators with quantitative RT-PCR and ELISA. Results: Wounds treated with fibronectin hydrogel demonstrated significantly faster wound closure and decreased scarring than wounds treated with PBS hydrogel. On postoperative day 21, the mean percentage of wound area relative to original wound size was significantly higher in the control wounds (21.3% ± 2.8%) than in the fibronectin-treated wounds (4.7 ± 1.0%). By the experimental endpoint on postoperative day 28, the mean percentage of control wound area was 6.8% ± 2.9% while all fibronectin-treated wounds were fully healed. Picrosirius red staining demonstrated that the fibronectin-treated wounds had decreased total scar area (9.9 ± 3.0 mm2) compared to control wounds (38.1 ± 3.6 mm2). In addition, fibronectin hydrogel treatment was associated with decreased levels of radiation-induced inflammatory mediators. RT-qPCR of samples from fibronectin-treated wounds had significantly lower mRNA levels of TGF-β1 (0.45 ± 0.09) compared to levels in control wounds (1 ± 0.13). Similarly, RT-qPCR data revealed that relative mRNA levels of SMAD3 were significantly lower in fibronectin-treated wounds (0.34 ± 0.11) than in control wounds (1 ± 0.43). Lastly, protein level correlation with ELISA identified significantly lower TGF-β1 concentrations in fibronectin-treated wounds (2682 + 515.83 pg/mL) compared to control wounds (5244.5 + 700.08 pg/mL). Conclusion: Hydrogel-facilitated delivery of fibronectin significantly improved the rate and quality of wound healing in a porcine chronic irradiation wound model. Thus, this novel mechanism of fibronectin supplementation demonstrates potential for treating these otherwise nonhealing wounds.